The Relationship Between Loneliness And Pubg Online Game Addiction In Early Adulthood In Padang City - Pusparini, Indri; Farah Aulia (In Trend : International Journal of Trends in Global Psychological Science and Education, 2025)
This research is motivated by the phenomenon of increasing online game addiction behavior among young adults in Padang City, especially the online game Player Unknown's Battle Ground (PUBG). This research aims to determine the relationship between loneliness and online game addiction in early adulthood in Padang City. The method used is a quantitative method with a correlational quantitative design. The subjects found in this study were 192 early adults in Padang City using purposive sampling as the sampling technique. The data collection method in this research was by using the UCLA Loneliness Scale and Game Addiction Scale (GAS) measuring instruments. Data analysis uses product moment correlation techniques. The results of this research hypothesis test obtained r = 0.536 with a significance value of p = 0.000. These results show that there is a significant positive relationship between loneliness and online game addiction in early adulthood in Padang City, meaning that the higher a person's feeling of loneliness, the higher the online game addiction will be.